PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN KOTAK TELUR PADA PT MEGA SARI AGUNG SEJAHTERA LANGKAT MEDAN - Andreyani, Graciela; Rendy, Rendy; Nyonata, Ricky Anderson; Ardiles, Zikho; Anggoro, Muhammad Agung (EDUTECH CONSULTANT, 2019)
This study aims to test and analyze the effect of product quality and service quality on egg box customer satisfaction at PT Mega Sari Agung Sejahtera Langkat Medan. The analytical method is multiple linear analysis. The population is customers at PT Mega Sari Agung Sejahtera Langkat Medan totaling 276 people. The sample research was 163 customers of PT Mega Sari Agung Sejahtera Langkat Medan. The conclusion showed that product quality and service quality partially and simultaneously had an effect on egg box customer satisfaction at PT Mega Sari Agung Sejahtera Langkat Medan. The test results of the determination coefficient above is the amount of adjusted R Square is 0.205, then the influence of product quality and service quality on egg box customer satisfaction at PT Mega Sari Agung Sejahtera Langkat Medan is 20.5% while the remaining 79.50% is influenced by other factors which was not examined in this study.